Determinants of Profitability, Firm Size, and Institutional Ownership Moderated by Capital Structure on Stock Returns - Satria Fajar Maulana; Pardomuan Sihombing (International Journal of Applied Management and Business, 2024)
The study was conducted to examine the influence of several factors that are suspected to affect the health care sector's stock returns, moderated by the capital structure proxied by the debt to equity ratio (DER). The population used in this research were seventeen companies, and the samples that match the research criteria were seven health care companies listed on the Indonesian stock exchange between 2018-2022. The research used panel data analysis techniques, and utilizes financial reports. The results of this study y indicate that profitability proxied by the return on equity (ROE) and institutional ownership has a positive influence, and DER has a negative influence on the stock return, while the firm size do not has significant effect on the stock return. The ROE and firm size are moderated by capital structure in their influence on the stock return. The findings of this study suggest that in maximizing the stock return in the health care sector's, companies need to increase profits, have a high level of institutional ownership and maximize sources of funds for the operational activities, as well as optimizing the use of debt to invest in assets.